2018
DOI: 10.3390/ijms19071883
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic Acid Induces Resistance in Rubber Tree against Phytophthora palmivora

Abstract: Induced resistance by elicitors is considered to be an eco-friendly strategy to stimulate plant defense against pathogen attack. In this study, we elucidated the effect of salicylic acid (SA) on induced resistance in rubber tree against Phytophthora palmivora and evaluated the possible defense mechanisms that were involved. For SA pretreatment, rubber tree exhibited a significant reduction in disease severity by 41%. Consistent with the occurrence of induced resistance, the pronounced increase in H2O2 level, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 80 publications
3
20
0
1
Order By: Relevance
“…Additionally, Xu and Tian [ 70 ] reported that treatment with salicylic acid increased the CAT activity and stimulated the expression of CAT genes in sweet cherry fruits. On the other hand, pre-harvest spraying of rubber trees with salicylic acid induced the accumulation of catalase and peroxidase in the leaves [ 71 ]. Additionally, Hortensia et al [ 72 ] observed that the exogenous application of chemical elicitors such as chitosan and salicylic acid during different stages in the development of tomato fruits significantly increased the activity of catalase and peroxidase enzymes in the fruit tissue.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, Xu and Tian [ 70 ] reported that treatment with salicylic acid increased the CAT activity and stimulated the expression of CAT genes in sweet cherry fruits. On the other hand, pre-harvest spraying of rubber trees with salicylic acid induced the accumulation of catalase and peroxidase in the leaves [ 71 ]. Additionally, Hortensia et al [ 72 ] observed that the exogenous application of chemical elicitors such as chitosan and salicylic acid during different stages in the development of tomato fruits significantly increased the activity of catalase and peroxidase enzymes in the fruit tissue.…”
Section: Resultsmentioning
confidence: 99%
“…Contrasting evidence exists about the role of SA signaling during Phytophthora infection. Whereas SA-pretreatment on rubber tree reduced the disease symptoms against P. palmivora [ 52 ], P. cinnamomi attack on chestnut did not alter SA levels [ 53 ]. Interestingly, we detected increased SA levels in stem sections both proximal and distal to the infection ( Figure 6 B), indicating that P. cinnamomi mounts a defense response similar to that triggered by biotrophic pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in bacterivore nematodes with the conversion of rainforest into plantations may have been due to the reduction of certain bacterial groups, especially in rubber plantations. Rubber plants produce salicylic acid to control microbial pathogens (Kästner et al, 2014;Deenamo et al, 2018) and this may reduce certain prey species of bacterivores. However, in general, the abundance and diversity of bacteria benefitted from the conversion of rainforest into plantations, presumably due to fertilizer application and liming (Ettema et al, 1999;Schneider et al, 2015).…”
Section: Nematode Functional Diversitymentioning
confidence: 99%